Fetus morphology changes by second‐trimester ultrasound in pregnant women drinking alcohol. (27th February 2019) - Ferraguti, Giampiero; Merlino, Lucia; Battagliese, Gemma; Piccioni, Maria Grazia; Barbaro, Greta; Carito, Valentina; Messina, Marisa Patrizia; Scalese, Bruna; Coriale, Giovanna; Fiore, Marco; Ceccanti, Mauro
Abstract: Fetal alcohol spectrum disorders (FASDs) are a group of negative conditions occurring in children exposed to alcohol during gestation. The early discovery of FASD is crucial for mother and infant follow‐ups. In this study, we investigated in pregnant women the association between urine ethylglucuronide (EtG—a biomarker of alcohol drinking) and indicators of the physical characteristics of FASD by prenatal ultrasound in the second trimester of gestation. We also correlated these data with the AUDIT‐C, T‐ACE/TACER‐3, TWEAK, and food habit diary, screening questionnaires used to disclose alcohol drinking during pregnancy. Forty‐four pregnant women were randomly enrolled and examined for ultrasound investigation during the second trimester of gestation. Urine samples were provided by pregnant women immediately after the routine interviews. EtG determinations were performed with a cutoff established at 100 ng/mL, a value indicating occasional alcohol drinking. Fifteen of the enrolled pregnant women overcame the EtG cutoff (34.09%). Analysis of variance (ANOVA) revealed that the fetuses of the positive EtG pregnant women had significantly longer interorbital distance and also significantly increased frontothalamic distance ( P 's < 0.02). Quite interestingly, no direct correlation was found between EtG data and both food diary and AUDIT‐C. However, a significant correlation was observed between urinary EtG and T‐ACE ( r  = 0.375; P  = 0.012) and between urinary EtG and TWEAK ( r  = 0.512; P  < 0.001) and a concordance with all questionnaire for EtG values higher than 500 ng/mL. This study provides clinical evidence that the diagnosis of maternal alcohol consumption during pregnancy by urine EtG may disclose FASD‐related damage in the fetus. Abstract : Pregnant women at the fourth month of gestation, positive to urine ethylglucuronide (EtG), a biomarker of alcohol consumption, display fetuses with morphological parameters resembling those of fetal alcohol spectrum disorders (FASDs), as disclosed by in‐depth ultrasound investigation. Only minor correlations between fetus changes and screening questionnaires to detect alcohol drinking during gestation were revealed, exclusively for high amounts of alcohol consumption.